FAMILY RESILIENCE REVIEWED FROM THE PSYCHOSOCIAL DIVERSITY OF THE RESIDENTS OF KAMPUNG KB CIPTA RASA CIREBON CITY - Novianti, Herny; Mukti, Taquddn B.Abd (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2025)
Family resilience is the ability of a family to adapt and survive in the face of various challenges. Psychosocial diversity, including factors such as social support, family communication, and emotional well-being, plays an important role in shaping family resilience. This research aims to analyze family resilience based on psychosocial diversity. The research was conducted using a survey method with a cross-sectional design. Data collection was carried out by distributing an instrument consisting of 23 items covering three aspects of family resilience, namely: family belief system, organizational patterns, and communication process to families with adolescent children. The instrument content validation stage was done by 2 reviewers, then the results of the review were processed using the Content Validity Item (CVI) Technique from Lewis R. Aiken. The respondents were 129 people from families of fishermen, laborers, and private employees who live in Warga Kampung KB Cirebon City, who were taken using the proportionate stratified random sampling technique. The data collected were tested for normality using the Kolmogorov-Smirnov test. The results of the analysis showed that there were significant differences in family resilience between families of fishermen, laborers, and private employees. The highest resilience score for fishermen's families was in the aspect of family belief system and organizational patterns, this is because many fishing communities have a long history and a rich culture in the values of togetherness and mutual cooperation. These values are instilled from an early age and become a strong foundation in building family resilience. While the highest resilience score for private employee families was in the aspect of communication patterns. This is because private employees are accustomed to working in an environment that emphasizes effective communication, collaboration, and professional development, so that it is applied in their family life. The implication of this study is that family resilience can be interpreted based on the background of psychosocial diversity.